2019
DOI: 10.1186/s12910-019-0361-2
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of family in the Dutch practice of euthanasia and physician assisted suicide: a systematic mixed studies review

Abstract: Background Family members do not have an official position in the practice of euthanasia and physician assisted suicide (EAS) in the Netherlands according to statutory regulations and related guidelines. However, recent empirical findings on the influence of family members on EAS decision-making raise practical and ethical questions. Therefore, the aim of this review is to explore how family members are involved in the Dutch practice of EAS according to empirical research, and to map out themes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 99 publications
1
57
0
3
Order By: Relevance
“…In addition, empirical studies show that while some patients wish to have full control in the deliberative process, others prefer to defer decision-making to their family members or, at least, to consider their interests extensively [39,40]. In end-oflife care, healthcare staff and family are often intimately involved, all being individuals that may affect, and be affected by, the patient's autonomous decisions [21,41,42].…”
Section: Autonomy Is Not Exercised By Patients Existing In a Social Amentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, empirical studies show that while some patients wish to have full control in the deliberative process, others prefer to defer decision-making to their family members or, at least, to consider their interests extensively [39,40]. In end-oflife care, healthcare staff and family are often intimately involved, all being individuals that may affect, and be affected by, the patient's autonomous decisions [21,41,42].…”
Section: Autonomy Is Not Exercised By Patients Existing In a Social Amentioning
confidence: 99%
“…Relational theorists react against the current ethical and legal framework generally conceived of as a dyad between patient and physician; however, a patient-doctorfamily triad seems more appropriate in characterizing what actually happens in clinical practice [40]. In the triad model, the family is not necessarily perceived of as a threat to autonomy.…”
Section: Family and Other Personal Relationshipsmentioning
confidence: 99%
“…2 However, many have identified that the experiences of family members and HCPs of people who have been found eligible for, or have received, assisted dying need to be better understood and addressed in institutional policies and care plans. 1,3 6…”
Section: Experiences Of Family Members and Healthcare Providersmentioning
confidence: 99%
“…In the Netherlands, the first country to legalize euthanasia, EAS accounted for 4.6% of all deaths in 2015. 1 Conversely, in individuals with mental disorders, EAS remains a rare practice (in the Netherlands, about 1% of all EAS cases per year). 2 However, the awareness and consideration of this option by patients, 3 and the total number of granted cases are steadily growing, despite the lower probability of proceeding with EAS after the request by this population.…”
Section: Introductionmentioning
confidence: 99%